WEBSITE-BASED E-MODULE DEVELOPMENT TO IMPROVE STUDENTS' COGNITIVE LEARNING OUTCOMES ON FISH PRODUCT PRODUCTION MATERIALS - Nurul Fadhillah; Sri Handayani; Mustika Nuramalia Handayani (PEDAGOGIA, 2022)
Decreased learning motivation and enthusiasm of students of class XI APHP at SMKN 2 Cilaku Cianjur in the learning process during the Covid-19 pandemic, causing a decrease in value in the cognitive aspect. In addition, the limited materials and learning media used by teachers contain students difficulty in understanding the material taught. Efforts made by researchers to overcome these problems are to develop website-based e-modules that can be accessed online to improve student learning outcomes. The purpose of this research includes (1) Knowing the feasibility of website-based e-modules used in the distance learning on fish production materials, (2) Knowing the learning outcomes of practical classes students using website-based e-modules and control classes that use power point after the implementation of distance learning activities on fish production materials reviewed from the cognitive aspect, and (3) Knowing the difference in the learning outcomes of practical classes students whose website based e-modules and control classes that use power points after the implementation of distance learning activities on fish production materials reviewed from the cognitive aspect. The development of this website-based e-modules uses an ADDIE model research design with several stages, including Analysis, Design, Development, Implementation, and Evaluation. Website-based e-modules developed are then implemented with distance learning to determine students’ learning outcomes via Whatsapp video call connected to the Facebook application using quasi-experiment research – nonequivalent control group design. The result showed that the website-based e-modules were declared “Viable” by a media expert, declared “Very Viable” by a material expert and linguist expert, and the results of product trials were declared “Very Viable” by students.